Energetic and exergetic investigations of an innovative light-based hydrogen production reactor - Acar, Canan; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
In this study, it is aimed to thermodynamically study and experimentally test a continuous type hybrid photoelectrochemical hydrogen production system. The hybrid system considered in this study is capable of enhancing solar spectrum utilization via the combination of photocatalysis and PV/T. In addition, the system eliminates the electron donor requirement of photocatalysis by employing photoelectrodes. Which, as a result, risk of potentially harmful pollutant emissions is reduced. In this study, the present system is investigated in electrolysis operation under three different inlet mass flow rates (0.25, 0.50, and 0.75 g/s). The experimental results are compared to the thermodynamic model outputs. Parametric studies are conducted by changing the inlet mass flow rate from 0 to 1 g/s. The present experimental results suggest that the highest hydrogen production rate is observed at 0.75 g/s inlet mass flow rate, which is 2.43 mg/h. The highest energy and exergy efficiencies are calculated at 0.25 g/s, which are 36% and 32%, respectively. Furthermore, thermodynamic model outputs are confirmed to have a good agreement with the experimental results. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Energy; Exergy; Hydrogen; Photoelectrochemical; Sustainability; Solar; HYBRID PHOTOELECTROCHEMICAL SYSTEM; P-TYPE CU2O; FOSSIL-FUELS; H-2 EVOLUTION; WATER; PHOTOCATALYST; EMISSIONS; MEMBRANE; Chemistry; Electrochemistry; Energy & Fuels